Optimalisasi Pola Perawatan Dan Perbaikan Terencana Sistem Pendingin (Cold Storage) 70 Ton Berdasarkan Analisa Keandalan - Abraham Manuhutu (Industrial Engineering Study Program, Pattimura University, 2012)
To support production process keep going from engine stuck, we have to devise a maintenance action or replacement of a damaged engine coolant (cold storage). If the maintenance alternatively exist longer, it will increase prevented-maintenance cost. So need to find an interval of maintenance and repair to minimize total cost of maintenance and repair by using reliability analyse. In determining interval time of optimum maintenance and repair to critical spare part , reliability analyse is applied against those components by using available downtime data as a premise to find the time of optimum maintenance and repair. The calculation result of reliability value against the critical components, are expected as input to devise strategy of maintenance and repair optimizely. Optimum determining interval time of maintenance and repair optimizely in this research recommended each components reliability index 0.1 with the interval time of maintenance and repair component Exhaust valve compressor & Intake valve compressor are on the day 450th, Expansion valve component is on the day 630thand Ring set compressor component is on the day 1170thwith time interval one year are optimum policy.